Balloon Test Occlusion for an Option to Decide Whether Simple ICA Ligation is Better Option than Trapping and High Flow Bypass of The Giant ICA Cavernous Aneurysm - Rajbhandari, Saujanya; Rajbhandari, Pravesh; Shrestha, Pranaya; Pant, Basant; Neupane, Anish (Nepal Journal of Neuroscience, 2017)
Balloon Test occlusion (BTO) is a preoperative angiographic test used to estimate the risk of stroke after permanent therapeutic occlusion of an internal carotid artery (ICA) involved by aneurysms. Temporary balloon occlusion at the cavernous ICA aneurysm neck was performed in an attempt to assess the adequacy of cross flow from the opposite ICA. Adequate fl ow following BTO are preferred to have simple ICA ligation and incase of those who did not pass BTO trapping and high flow bypass is preferred .We have done Right ICA Ligation on our case report. Nepal Journal of Neuroscience, Vol. 14, No. 2, 2017 Page:32-35